Gastro-Cosmopolitan in Osing Coffee - Zulfikar, Fachri (Sebelas Maret University (UNS), 2020)
This article argues that coffee is a transnational and global project in the colonial period to the present. The dramatic expansion of coffee in this period was partly brought about by foreign colonialism, and was emulated by the osing tribe. The Osing are exposed to a new culinary culture and make a new culture that is maintained until now. The culture of drinking coffee made a new festival called